Intervention to Reduce Anxiety in Postpartum Mother - Denis Mulanita Pratiwi; Sri Rejeki; Achmad Zulfa Juniarto (Universitas Muhammadiyah Semarang, 2021)
Postpartum stress mostly experienced by first-time mothers. This stressful condition indicates that some new mothers experience emotional changes, sometimes feeling happy and at times almost feeling sad for no reason. This study aims to understand a deeper understanding of interventions for postpartum anxiety. A literature review was conducted by looking for literature related to the theme taken. The articles obtained were 9 quantitative studies, 7 articles from Indonesia and 2 articles from other countries. Most interventions are massage therapy and various types of relaxation (aromatherapy, hypnotherapy, yoga) to reduce the level of anxiety of postpartum mothers. This review helps provide several interventions that can be carried out on postpartum mothers in a nonpharmacological, simple and effective interventions that can be carried out in postpartum mothers in reducing the level of anxiety of postpartum mothers, besides that it can improve sleep quality, reduce levels of depression, reduce stress, can increase breast milk production and increase comfort in postpartum mothers.